Draft Genome Sequence of the Mycobacterium tuberculosis Clinical Isolate C2, Belonging to the Latin American–Mediterranean Family - Liao, Yu-Chieh (American Society for Microbiology, 2014)
Tuberculosis remains a major infectious disease in Taiwan. Here we present the draft genome sequence of the Mycobacterium tuberculosis C2 strain, belonging to the Latin American–Mediterranean lineage. The draft genome sequence comprises 4,453,307 bp with a G+C content of 65.6%, revealing 4,390 coding genes and 45 tRNA genes.